PENGARUH STRATEGI REACT DAN SIKAP SISWA TERHADAP MATEMATIKA DALAM PENINGKATAN KEMAMPUAN KONEKSI MATEMATIKA SISWA SMA - Friska Bernadette Siahaan; Sahat Saragih; Pargaulan Siagian (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2010)
The artificial experiment research with the pretest-post test control group design is aimed at knowing the difference of mathematics connecting ability between the students though with the REACT strategy approach and the students taught with conventional learning. The subject of the research are the students in grade XI science from Senior High School State and private school students in Sub Rayon 07 Medan which are acreditated A and B as the subject research. Each school is chosen randomly to represent the school accreditated A and B. The class from grade XI science is also chosen randomly with the determination one for experiment class and the other for control class. The instrument used in this research is the mathematics connecting ability test which has already been testedand the result has met validity condition and the reliability coefisien is 0,56(modest). The research result shows that the students taught with the REACT strategy is significantly better in increasing the mathematics connecting ability than students taught with conventional learning method. It is better not  only based on the whole activity but also based on the students attitude against mathematics (positive, negative). Based on this research, it is suggested that all the teacher who teach mathematics at Senior High School can make the REACT strategy as an alternative in delivering the mathematics and can socialize the use of it in Senior High School.lesson.